An update on treatment of ulcerative colitis. (3rd June 2019) - Annese, Vito
ABSTRACT: Introduction : Ulcerative colitis is a lifelong chronic inflammation of colon-rectum with prevalence on the rise. It has a profound impact on patients' quality of life and is a burden on direct and indirect health-care costs. Therapeutic strategies are progressively evolving because of the successful expansion of therapeutic armamentarium. Areas covered : A structured literature search has been conducted on medical therapy, with a focus on available guidelines and technical reviews on the topic. Traditional therapy includes 5-aminosalycilic acid (5-ASA) which is effective and disease-modifying in approximatively 50% of patients. For many years systemic corticosteroids and immunosuppressants such as thiopurines, methotrexate, and cyclosporine have been used when 5-ASA fails. In the last two decades, a great breakthrough was the progressive availability of biologics, 'topical' corticosteroids and more recently small molecules. However, unmet needs still exist with 10–15% of patients still requiring colectomy. In this review, we have evaluated the available therapeutic options and their positioning based on patient's profiling in terms of disease extension, activity, disease behavior and response to therapy. Expert opinion : There are still gaps in term of risk stratification to pinpoint patients that may benefit from an early more 'aggressive' therapy. More information is needed on fecal microbiota transplantation and direct comparisons among available and future biologic therapy.